Comparison of organic coolants for boiling cooling of proton exchange membrane fuel cell. (1st March 2023) - Li, Qingshan; Wang, Chenfang; Wang, Chunmei; Zhou, Taotao; Zhang, Xianwen; Zhang, Yangjun; Zhuge, Weilin; Sun, Li
Abstract: Cooling and temperature homogeneity are the key technical problems for the proton exchange membrane fuel cell (PEMFC) thermal management. In this paper, a one-dimensional model of a PEMFC with phase-change cooling (flow boiling cooling) is proposed for PEMFC thermal management, and the heat transfer of microchannel flow boiling is integrated with PEMFC cooling. Five organic coolants (Novec 649, HFC-365mfc, HFE-356mec, HFE-347pcf2, and HFE-7100) and single-phase water are compared by the PEMFC average temperature of the catalyst layer (ATCL) and temperature difference of the catalyst layer (TDCL). The PEMFC temperature characteristics with organic coolant are investigated in detail. The results indicate that HFE-7100 exhibited the lowest ATCL and minimum TDCL among the coolants. The maximum TDCL of HFE-7100 is 5.5 K at current density of 1.2 A/cm 2, which can completely keep the PEMFC operating temperature at proper and uniform conditions. The minimum ATCL of Novec 649 is over 353 K, which dissatisfies the cooling demand. The TDCLs of PEMFCs with different organic coolants have a minimum value when the coolant outlet vapour mass fraction is 0.4. Temperature uniformity should be the most important factor for mass flow control in PEMFCs using organic coolants. Highlights: A proton exchange membrane fuel cell phase-change cooling model is proposed. Boiling cooling for fuel cell has lower flow rate sensitivities. Minimum temperature difference along channel appears at 0.4 mass fraction. HFE-7100 coolant maximum temperature difference is 5.5 K.